Combinatorial Investigation of the Ni–Ta System via Correlated High‐Speed Nanoindentation and EDX Mapping (Small Methods 2/2022). Issue 2 (17th February 2022) - Wheeler, Jeffrey M.; Gan, Bin; Spolenak, Ralph
Abstract : Inside Front Cover In article number 2101084, Wheeler and co‐workers demonstrate a direct method for correlating compositional and mechanical datasets from high‐speed nanoindentation and EDX maps. They demonstrate this method combinatorially on a Ni–Ta diffusion couple, which includes five intermetallic phases with varying properties. This method yields paired compositional and mechanical data from any microstructural cross‐section, independent of spatial distribution and morphology.